Cara untuk Memperoleh Bentuk dan Ukuran Gigi Seperti Gigi Asli pada Pembuatan Gigi Tiruan Lengkap Imediat - Titi S. Soebekti (Journal of Dentistry Indonesia, 2015)
There is a very close relationship between the form and size of the anterior teeth and the patient's personality. In order to fulfill the patient's expectation to have his immediate complete denture with the same form and shape of his natural teeth, an impression was made before the teeth were extracted. This impression was poured with the same tooth colored self curing acrylic resin in the anterior teeth. After the resin set, the impression was fully poured with hard stone. With this method, a duplication of the natural anterior teeth was made and those teeth were set up in a better position int he immediate denture.